ضمانات وحوافز المستثمر الأجنبي في ظل القانون رقم 22-18 - قساس, أميمة (University of Eloued جامعة الوادي, 2023)
تعتبر الاستثما ا رت الأجنبیة إحدى أهم مصادر التمویل الدولیة وقناة أساسیة لتدفق رؤوس الأموال والخبرة العلمیة والفنیة والتكنولوجیة ،لذلك سعت الج ا زئر كغیرها من الدول النامیة إلى توفیر بیئة أعمال جاذبة ومستقطبة لهذه الاستثما ا رت لكونها وسیلة بدیلة وناجعة تغني عن 18 المتعلق بالاستثمار الذي قدم مجموعة من - قطاع المحروقات وذلك ما ترجمه القانون 22 الضمانات للمستثمرین الأجانب (قان ونیة ،مالیة وقضائیة) وأقر جملة من الحوافز والامتیا ا زت ذات الطابع المشجع للاستثمار في الج ا زئر (ضریبیة وجم ركیة ،تمویلیة وإج ا رئیة).Foreign investments are considered one of the most important sources of international financing and an essential channel for the flow of capital and scientific, technical and technological expertise. Therefore, Algeria, like other developing countries, has sought to provide an attractive and polarizing business environment for these investments, as it is an alternative and effective means that dispenses with the hydrocarbon sector, as translated by Law 18-22 related to With the investment that provided a set of guarantees to foreign investors (legal, financial and judicial) and approved a number of incentives and privileges of an encouraging nature for investment in Algeria (tax and customs , financing and procedural ).
مذكرة ماستر
Keywords: بیئة استثماریة جذابة -الاستثمار الأجنبي – المستثمر الأجنبي – الضمانات – الحوافز والامتیا ا ز; Attractive investment environment - Foreign investment - Foreign investor - Guarantees – Incentives and Privileges.